Differential medium for the detection of the food and beverage spoilage yeast Zygosaccharomyces bailii - Schuller, Dorit Elisabeth (1997)
Resumo da comunicação apresentada sob forma de painel, "18th International Specialized Symposium on Yeasts : Yeast Nutrition and Natural Habitats", 1997, Bled, Eslovénia.